2016
DOI: 10.1186/s12884-016-1170-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced neonatal mortality in a regional hospital in Mozambique linked to a Quality Improvement intervention

Abstract: BackgroundNeonatal mortality remains a serious health issue especially in low resource countries, where 99% of neonatal deaths occur. Doctors with Africa CUAMM is an Italian non-governmental organization in the field of healthcare that has been working in Africa since 1955. In Mozambique, at the Central Beira Hospital (CBH), it has a project with the aim of supporting the neonatal intensive care unit (NICU) and the Obstetrical Department of the CBH through a multi-level intervention. Our aim was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 21 publications
(11 reference statements)
1
28
0
Order By: Relevance
“…Low proficiency with BMV immediately after training suggests that educational programmes should emphasize the learning of such a technique, including methods for improving ventilation when it is initially ineffective. Our data show a lower mortality rate after the low-dose/ high-frequency training, but this is likely associated with hospital-level quality improvements (including interventions regarding infrastructure, equipment and clinical protocols) that were implemented after the NRP course [25].…”
Section: Discussionmentioning
confidence: 94%
“…Low proficiency with BMV immediately after training suggests that educational programmes should emphasize the learning of such a technique, including methods for improving ventilation when it is initially ineffective. Our data show a lower mortality rate after the low-dose/ high-frequency training, but this is likely associated with hospital-level quality improvements (including interventions regarding infrastructure, equipment and clinical protocols) that were implemented after the NRP course [25].…”
Section: Discussionmentioning
confidence: 94%
“…Similar observations were made following improved infrastructure, equipment and clinical protocols in an NNU in Mozambique where the mortality rate for asphyxia (34% vs 19%), sepsis (39% vs 28%) and prematurity (43% vs 33%) decreased significantly. 6 It is estimated that around one-quarter of neonatal deaths occur in the first day; therefore, emphasis on improving neonatal care needs to extend to the staff in the labour and postnatal ward to reduce neonatal mortality. 2 …”
Section: Reducing Mortalitymentioning
confidence: 99%
“…Where hospital-based neonatal care has been implemented in LICs, significant impacts on mortality have been demonstrated. 6–9 If the unacceptable number of neonatal deaths are to be reduced, in addition to improving community neonatal care and emergency care at the time of delivery, hospital-based neonatal care needs to be developed to ensure a full cycle of care. Some frameworks already exist to evaluate and improve neonatal care, but they focus primarily on obstetric-led neonatal emergency management and not on ongoing specialised neonatal care.…”
Section: Introductionmentioning
confidence: 99%
“…7 A group from India described how the creation of an SNCU, as opposed to treating neonates in the paediatric ward, in a West Bengal district hospital reduced intra-hospital neonatal mortality from 31% to 25% within 2 years. 19 SCNUs that are supported by other actors showed a reduction in intra-ward mortality: a Mozambican SNCU supported by Collegio Universitario Aspiranti Medici Missionari-Doctors for Africa brought mortality down from 26% to 13%, 8 and an MSF-managed SNCU in South Sudan (not included in this study), which excluded babies weighing 1250 g from admission, reported a reduction of mortality from 19% to 11% within 3 years. 10 Facility exit outcomes of neonatal units not only reflect the quality of nursing and medical care at the unit, they are also highly dependent on the patient population and on the quality of intrapartum and immediate post-partum interventions.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…4 There are descriptions of SNCUs and outcomes of their patients in resource-limited, but mostly stable, settings. [5][6][7][8] Around 2009, Médecins Sans Frontières Operational Centre Brussels (MSF-OCB), an international non-governmental organisation providing humanitarian aid and free medical assistance to populations in distress, started offering specialised neonatal care in resource-limited settings, and has increased this activity over time. MSF-managed SNCUs are integrated into district or regional hospitals: some are located in conflict settings, and most operate in remote areas where no other supporting health actors are present.…”
mentioning
confidence: 99%